Farmers’ perceptions on trypanosomosis and trypanotolerance character of the taurine Sheko - Taye, T.D.; Ayalew, W.; Hegde, P.B. (Springer, 2012)
In the humid and subhumid tropics, trypanosomosis is an economically important zoonotic protozoan disease of the commonly kept farm animal species and their wild relatives. For example, more than 20% of the humid western and southwestern Ethiopia, which is home to more than 14 million heads of cattle, is under varying levels of trypanosomosis risk. Our study was, therefore, initiated to document farmers’ perception on trypanosomosis and Sheko’s trypanotolerance character. Our findings showed that trypanosomosis was the most frequently reported cattle disease in the Bench Maji Zone. Accordingly, 76.7% of the farmers reported the epidemiological importance of trypanosomosis, and they also noted that trypanosomosis on average accounted for 63.0% of annualized cattle death. The reported signs of trypanosomosis and trypanotolerance indicators were consistent with literature reports. Moreover, 66.7% of the farmers reported Sheko’s trypanotolerance character. In the course of time, smallholder farmers have developed ethnoveterinary practices that are mainly used to prevent the landing of vector flies on the animal. Wet and warm seasons of the year, i.e., spring and, to some extent, the beginning of summer and autumn, were reported as peak periods of trypanosomosis risk. Therefore, this showed the need for incorporating farmers’ knowledge in trypanosomosis control programs.